2022
DOI: 10.1021/acsphotonics.2c00496
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Sky-Blue Perovskite Light-Emitting Diodes via the Trade-Off between the Electron–Phonon Coupling Loss and Defect Passivation

Abstract: The efficiency of blue perovskite light-emitting diodes (PeLEDs) is lagging far behind their green and red counterparts. Here, we demonstrate high-efficiency sky-blue PeLEDs by employing pseudohalide thiocyanates, which are ammonium thiocyanate (NH4SCN), methylammonium thiocyanate (MASCN), and guanidine thiocyanate (GASCN), as additives in a quasi-two-dimensional cesium lead halide perovskite emission layer. Although the thiocyanate incorporation can modify the formation energy to induce more n = 1 phases that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…After storing the films for 5 days under ambient conditions, the PL properties were only slightly altered (e.g., red shift in the emission peak and 10% drop in the PLQY), showing enhanced stability compared to pristine NCs, which exhibited a red shift of 20 nm in the emission and a PLQY reduction of more than 50%. Notably, previous studies on hybrid perovskites have demonstrated improvement in PLQY up to 60% upon the incorporation of SCN − , 43,44 whereas inorganic perovskite have shown up to 45%, 45 suggesting that hybrid pervovskite have more potential for further optimization. Upon post-treatment, the absorption spectra exhibited a sharp excitonic peak at 420 nm with an absorption edge at 512 nm, corresponding to the emission peaks at 435 (low intensity) and 520 nm, respectively (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After storing the films for 5 days under ambient conditions, the PL properties were only slightly altered (e.g., red shift in the emission peak and 10% drop in the PLQY), showing enhanced stability compared to pristine NCs, which exhibited a red shift of 20 nm in the emission and a PLQY reduction of more than 50%. Notably, previous studies on hybrid perovskites have demonstrated improvement in PLQY up to 60% upon the incorporation of SCN − , 43,44 whereas inorganic perovskite have shown up to 45%, 45 suggesting that hybrid pervovskite have more potential for further optimization. Upon post-treatment, the absorption spectra exhibited a sharp excitonic peak at 420 nm with an absorption edge at 512 nm, corresponding to the emission peaks at 435 (low intensity) and 520 nm, respectively (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The superior defect tolerance properties of metal halide perovskites provide extremely narrow emission line widths with more saturated and richer colors when used as light-emitting materials . Meanwhile, metal halide perovskites have advantages of easily tunable emission color, high carrier mobility, and low-cost processing, making them suitable for the fabrication of a new generation of low-cost and high-performance LEDs for applications in advanced displays, lighting, and optical communications. , …”
Section: Introductionmentioning
confidence: 99%
“…1 Meanwhile, metal halide perovskites have advantages of easily tunable emission color, 2 high carrier mobility, 3 and low-cost processing, 4 making them suitable for the fabrication of a new generation of lowcost and high-performance LEDs for applications in advanced displays, lighting, and optical communications. 5,6 Since the first preparation of PeLEDs with green and red emission at room temperature in 2014, 7 great improvement has been achieved in the efficiency of monochromatic PeLEDs. 8−10 The highest efficiencies of sky-blue, green, and red PeLEDs reported so far are 14.71, 11 28.1, 12 and 23%, 13 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12 Concerning this issue, defect passivation has been developed to eliminate the influence of the shallow trap defects on the optical performance. The common strategies include ligand passivation 13,14 and epitaxial shell coating 15,16 through wet chemical processing as well as stoichiometric regulation via solid-phase synthesis. 17−19 However, the passivated wide band-gap II−VI semiconductors still suffer from the PL quenching during the rapid liquid−solid transition due to possible dimensional changes and ligand shedding.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning this issue, defect passivation has been developed to eliminate the influence of the shallow trap defects on the optical performance. The common strategies include ligand passivation , and epitaxial shell coating , through wet chemical processing as well as stoichiometric regulation via solid-phase synthesis. However, the passivated wide band-gap II–VI semiconductors still suffer from the PL quenching during the rapid liquid–solid transition due to possible dimensional changes and ligand shedding . In addition, stoichiometric regulation would introduce other types of defects due to the elemental imbalance, such as interstitial defects, resulting in difficult manipulation and greatly affecting the target optical properties. , …”
Section: Introductionmentioning
confidence: 99%